Several proteins derived from serum exosomes are potential biomarkers for diagnosis and progression of sudden sensorineural hearing loss - Li, Juanjuan; Bai, Suwen; Zhang, Peng; Zeng, Xianhai; Kong, Hui (Frontiers in Neurology, 2025)
BackgroundThis study aims to compare the protein expression profiles of plasma-derived exosomes in patients with sudden sensorineural hearing loss (SSNHL) and normal hearing control groups to identify exosome proteins that may be associated with SSNHL or serve as biomarkers for SSNHL.MethodsResearchers collected peripheral venous blood from SSNHL patients and healthy controls for exosome isolation. The isolated exosomes were identified through nanoparticle tracking analysis, transmission electron microscopy observation, and Western blotting, followed by total protein extraction for proteomic sequencing. Differential expression proteins (DEPs) were screened using the threshold criteria of p-value<0.05 and fold change (FC) > 1.2, with subsequent functional analysis. Ultimately, four exosomal DEPs-RPS2, RPL19, ACO2, and APOE-were selected and validated using ELISA.ResultsResearchers isolated exosomes from plasma and identified them through particle size analysis, morphological observation, and expression of exosome marker proteins. Comparative studies with healthy individuals revealed 363 DEPs in SSNHL. Additionally, 515 DEPs were identified in mild sudden deafness (MilSSNHL) and healthy controls, 982 in moderate cases (ModSSNHL) and healthy controls, and 1,161 in profound cases (ProSSNHL) and healthy controls. These proteins are involved in signaling pathways enriched by DEPs. Validation experiments demonstrated that the expression levels of these proteins consistently matched their sequencing results, ensuring high reliability. Furthermore, these candidate proteins show significant diagnostic potential for SSNHL.ConclusionThe four extracellular proteins identified in this study, including RPS2, RPL19, ACO2 and APOE, may be closely related to the occurrence and development of SSNHL or serve as biomarkers for the diagnosis and staging of SSNHL.